2020
DOI: 10.1111/eea.12902
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity and virulence of Nosema ceranae (Microsporidia) isolates obtained from various Apis mellifera morphotypes

Abstract: The infection of honey bees, Apis mellifera L. (Hymenoptera: Apidae), by the microsporidian Nosema ceranae is one of the factors related to the increase in colony losses and the decrease in honey production observed in recent years. However, these effects seem to differ depending on the climate zone. The range and prevalence of N. ceranae have increased significantly in the last decades, with different consequences in northern and southern temperate areas. The existence of various isolates of N. ceranae from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…The analysis using the COI-COII mitochondrial region was consistent with recently published works (Agra et al, 2018;Calfee et al, 2020;Porrini et al, 2020) that described the presence of genetic variability and a preponderant presence of African lineages (A1 and A4) in feral honey bee colonies mainly established in the north of Argentina. However, a saturation of AHBs in the north of Argentina previously described by Sheppard et al (1991) was not observed in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The analysis using the COI-COII mitochondrial region was consistent with recently published works (Agra et al, 2018;Calfee et al, 2020;Porrini et al, 2020) that described the presence of genetic variability and a preponderant presence of African lineages (A1 and A4) in feral honey bee colonies mainly established in the north of Argentina. However, a saturation of AHBs in the north of Argentina previously described by Sheppard et al (1991) was not observed in our study.…”
Section: Discussionsupporting
confidence: 89%
“…A positive relationship between geometric morphometry variables and apiary location could indicate the presence of an environmental effect, as well as other factors not directly assessed in this study (such as parental gene effects). In addition, we found that sensitivity decreases when analyzing morphometric differences between haplotypes, as non-significant differences were detected, in accordance with recent results by Porrini et al (2020). These results could be due to phenotypic similarity between A4 and A1 and the ongoing hybridization process present in the northern region of Argentina, and suggest that geometric morphometry would not be sufficiently sensitive as an indirect marker of mitochondrial haplotype for these populations, as proposed by Kandemir et al (2011) for other populations.…”
Section: Discussionsupporting
confidence: 88%
“…Larvae were sourced from an experimental apiary of Apis mellifera mellifera × Apis mellifera ligustica hybrids (Porrini et al., 2020), with sister queens placed at J.J. Nágera Coastal Station (38°10′60″ S; 57°38′10″ W), Universidad Nacional de Mar del Plata, Argentina. Larvae (L1) were randomly selected from combs belonging to three different colonies, following the method described by Crailsheim et al.…”
Section: Methodsmentioning
confidence: 99%
“…Larvae were sourced from an experimental apiary of Apis mellifera mellifera × Apis mellifera ligustica hybrids (Porrini et al, 2020), with sister queens placed at J.J. Nágera Coastal Station (38°10′60″ S; 57°38′10″ W), Universidad Nacional de Mar del Plata, Argentina.…”
Section: Larval Materialsmentioning
confidence: 99%
“…However, N. ceranae infections have been reported to be more severe in honey bee colonies than N. apis infections (Higes et al, 2008). In Argentina, genetic studies reported that the cosmopolite microsporidia species is N. ceranae (Medici et al, 2012;Porrini et al, 2020). In addition, other studies have concluded that nosemosis can act synergistically with other risk factors (Steinhauer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%